Neuroradiologic findings in polyarteritis nodosa. - Provenzale, J M; Allen, N B (American Journal of Neuroradiology, 1996)
PURPOSE To demonstrate the neuroradiologic findings in patients with polyarteritis nodosa.METHODS A review of hospital records for a 10-year period revealed 50 patients with a discharge diagnosis of polyarteritis nodosa. Thirteen patients had undergone neuroimaging, and abnormal findings were found in 5 cases; these were the subjects of this study.RESULTS All 5 patients had abnormal findings on CT scans, 3 had abnormal findings on MR images, and 1 had an abnormal finding on a cerebral angiogram. All patients had cerebral cortical or subcortical infarctions, and 1 also had small infarctions within the brain stem and cerebellum. One patient had cerebral angiographic findings of arteritis. The diagnosis of arteritis was considered probable or possible in 3 other patients. Three patients had echocardiographic evidence of concentric hypertrophy and a hypocontractile left ventricle resulting from polyarteritis nodosa-related hypertension. Cardiogenic embolism was considered the likely cause in 1 patient.CONCLUSION Small peripheral cerebral infarctions, consistent with an arteritis involving medium-sized and small arteries, were the most common finding. However, cardiogenic embolism should also be considered as a possible cause of cerebral infarction in patients with polyarteritis nodosa who have left ventricular dysfunction.